Modelling operation parameters of UAV on spray effects at different growth stages of corns - Yongjun, Zheng; Shenghui, Yang; Chunjiang, Zhao; Liping, Chen; Lan, Yubin; Yu, Tan (International Journal of Agricultural and Biological Engineering, 2017)
Abstract: Currently, unmanned aerial vehicles (UAVs) were widely applied to spray for pest and disease control. However, spray effect can be further improved by setting operation parameters more reasonably and scientifically. Therefore, this study attempts to derive the relationship between operation parameters and spray effect. Different growth stages were distinguished by various corn heights. A six-rotor UAV was operated at different heights and velocities to test pesticides spray effects for corns at different growth stages. Different plant canopy coverage rate and penetrating coefficients were obtained, according to which, the effects on droplet deposition rate caused by different UAVs’ operation parameters were analyzed. Droplet penetrating coefficients were applied as indexes to evaluate and select UAVs operation parameters for corns at different growth stages respectively. Mathematical models of droplet penetrating coefficients with UAVs operation parameters were established for corns at all growth stages. The determination coefficients (R2) of all models were greater than 0.90 and average relative errors were within 20%, which asserted high forecasting accuracy of droplet penetrating rate. With the help of the models, parameters like operating height away from the bottom of corns and UAVs velocities were further analyzed, which guided the optimization of parameter settings and selection of spray methods for corns at different growth stages.Keywords: multi-rotor unmanned aerial vehicle, spraying, parameter model, growth stage, cornDOI: 10.3965/j.ijabe.20171003.2578Citation: Zheng Y J, Yang S H, Zhao C J, Chen L P, Lan Y B, Tan Y. Modelling operation parameters of UAV on spray effects at different growth stages of corns. Int J Agric & Biol Eng, 2017; 10(3): 57–66.